Implementasi Sistem Monitoring Pembangunan Berbasis Kolaborasi untuk Optimalisasi Tata Kelola Pemerintah Kota Parepare - Nuranti, Eka Qadri; Intizhami, Naili Suri; Tunnisa, Khaera; Mar’atuttahirah,; Jefri, Muhammad Rivaldi; Anugrah, Muhammad; Alfian, Muhammad; Hakim, Lukman; Alfatih, Muhammad Aldi; Palaloi, Rahmat Eka Putra R (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to implement a Development Monitoring System based on collaboration between academics and the local government in order to improve reporting efficiency, data consistency, and information validity, while strengthening the capacity of government officials to support transparent and accountable governance. The program involved 14 officials from the Regional Development Planning Agency (Bappeda) of Parepare City. The implementation methods included needs analysis, system design, implementation, as well as training and technical assistance. Evaluation was conducted through pre-test and post-test assessments using the Quizizz application and user satisfaction questionnaires. The results showed an improvement in participants’ understanding, particularly in technical aspects, with an accuracy increase of 25% (from 64% to 89%). In addition, the level of user satisfaction was high, with the ease-of-use score reaching 4.50 out of 5, indicating that the system was easy to operate and well accepted by users. This program highlights the importance of collaboration between academics and local government in realizing data-driven development governance and has the potential to be further developed through integration with other systems, such as the Regional Innovation System and the Performance Indicator System.